Expression of the common acute lymphoblastic leukaemia antigen (CALLA gp100) in the brush border of normal jejunum and jejunum of patients with coeliac disease. Issue 9 (September 1985) - Trejdosiewicz, L K; Malizia, G; Oakes, J; Losowsky, M S; Janossy, G
Abstract : Expression of the gp100 common acute lymphoblastic leukaemia antigen (CALLA) was studied in the mucosa of the gut by means of indirect immunofluorescence on cryostat tissue sections with a panel of eight monoclonal antibodies to common acute lymphoblastic leukaemia antigen (anti-CALLA antibodies) and two antibodies to non-CALLA leukaemic antigens. Expression of CALLA was absent from normal stomach epithelium, adult and fetal colonic epithelium of normal histology, and colonic epithelium from patients with Crohn's disease or ulcerative colitis. By contrast, all eight anti-CALLA antibodies gave a characteristic reaction in normal adult and fetal small bowel mucosa, with specific localisation to the entire brush border of jejunal epithelium. Whereas seven of these antibodies reacted both with normal jejunal epithelium and with the damaged epithelium of patients with coeliac disease, antibody RFAL-2 reacted strongly only with histologically normal small bowel but more weakly in patients with coeliac disease to a degree related to the amount of histological abnormality. Expression of the moeity like CALLA identified with RFAL-2 was strongest in crypt epithelium and proportionally diminished along the villi according to the amount of histological damage in coeliac disease, being essentially absent in patients with "subtotal villous atrophy."